2023
DOI: 10.3390/ijms24108853
|View full text |Cite
|
Sign up to set email alerts
|

Physapruin A Exerts Endoplasmic Reticulum Stress to Trigger Breast Cancer Cell Apoptosis via Oxidative Stress

Abstract: Physalis plants are commonly used traditional medicinal herbs, and most of their extracts containing withanolides show anticancer effects. Physapruin A (PHA), a withanolide isolated from P. peruviana, shows antiproliferative effects on breast cancer cells involving oxidative stress, apoptosis, and autophagy. However, the other oxidative stress-associated response, such as endoplasmic reticulum (ER) stress, and its participation in regulating apoptosis in PHA-treated breast cancer cells remain unclear. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…ER stress inducer, tunicamycin, is a nucleotide antibiotic produced by actinomycetes. The mRNA and protein levels of ER stressresponsive genes (IRE1α and BIP) were upregulated in breast cancer cells [41]. The results showed that ER stress induced apoptosis in MDA-MB-231 by upregulating the expression of PERK, eIF2α, ATF4, CHOP, and caspase 4 that calpain could be a potential target for BC therapy [42].…”
Section: Breast Cancermentioning
confidence: 99%
“…ER stress inducer, tunicamycin, is a nucleotide antibiotic produced by actinomycetes. The mRNA and protein levels of ER stressresponsive genes (IRE1α and BIP) were upregulated in breast cancer cells [41]. The results showed that ER stress induced apoptosis in MDA-MB-231 by upregulating the expression of PERK, eIF2α, ATF4, CHOP, and caspase 4 that calpain could be a potential target for BC therapy [42].…”
Section: Breast Cancermentioning
confidence: 99%
“…11,12 In a study, it was shown that Physapruin A, which has an antiproliferative effect, exhibited ER stress-inducing function to promote the proliferation and apoptosis of breast cancer cells containing oxidative stress. 13 ER, stress results in the activation of the UPR, which plays a primary role in stress adaptation, inducing apoptosis in affected cells when stress is not resolved. 14,15 The UPR is controlled by protein kinase RNA-like ER kinase (PERK), inositol-requiring enzyme 1 (IRE1), and activating transcription factor 6 (ATF6).…”
Section: Introductionmentioning
confidence: 99%